The uniqueness of subunit α of mycobacterial F-ATP synthases: An evolutionary variant for niche adaptation - Ragunathan, Priya (2018)
The F1F0 -ATP (F-ATP) synthase is essential for growth of Mycobacterium tuberculosis, the causative agent of tuberculosis (TB). In addition to their synthase function most F-ATP synthases possess an ATP-hydrolase activity, which is coupled to proton-pumping activity. However, the mycobacterial enzyme lacks this reverse activity, but the reason for this deficiency is unclear. Here, we report that a Mycobacterium-specific, 36-amino acid long C-terminal domain in the nucleotide-binding subunit α (Mtα) of F-ATP synthase suppresses its ATPase activity and determined the mechanism of suppression. First, we employed vesicles to show that in intact membrane-embedded mycobacterial F-ATP synthases deletion of the C-terminal domain enabled ATPase and proton-pumping activity. We then generated a heterologous F-ATP synthase model system, which demonstrated that transfer of the mycobacterial C-terminal domain to a standard F-ATP synthase α subunit suppresses ATPase activity. Single-molecule rotation assays indicated that the introduction of this Mycobacterium-specific domain decreased the angular velocity of the power-stroke after ATP binding. Solution X-ray scattering data and NMR results revealed the solution shape of Mtα and the 3D structure of the subunit α C-terminal peptide 521PDEHVEALDEDKLAKEAVKV540 of M. tubercolosis (Mtα(521–540)), respectively. Together with cross-linking studies, the solution structural data lead to a model, in which Mtα(521–540) comes in close proximity with subunit γ residues 104–109, whose interaction may influence the rotation of the camshaft-like subunit γ. Finally, we propose that the unique segment Mtα(514–549), which is accessible at the C terminus of mycobacterial subunit α, is a promising drug epitope.